خصائص وتدبير أذيات الطلق الناري في منطقة الوجه والفكين - خليل, عبد الكريم; حداد, إبراهيم (Latakia University Journal -Medical Sciences Series, 2018)
هدفت هذه الدراسة الى تقييم تأثير أذيات الطلق الناري في المنطقة الوجهية- الفكية خلال الأزمة السورية الحالية بنوعية الأسلحة الحديثة المستخدمة والتظاهر السريري لهذه الاذيات (الرخو و العظمي) بالإضافة الى تقييم نوعية المعالجة الجراحية المقدمة للمرضى في ضوء الحاجة الى معالجات فعالة وناجحة. تألفت عينة البحث من 40 مريضا" تكبدوا أذية حربية راجعو على أثرها: - مشفى تشرين الجامعي – مشفى الأسد تم تقسيم المرضى حسب منطقة الاصابة ثم حددت خصائص الأذية والإجراء الجراحي بشكل مبكر لتخربات النسج الرخوة وفي نفس المرحلة للتخربات العظمية باستخدام الأشكال المختلفة للمثبتات المعدنية The aim of this study was To evaluate the effect of gunshot injuries in maxillofacial region in the context of Syrian crisis in terms of the quality of modern weapons which had used and the clinical demonstration of these injuries (soft and bone), in addition to evaluating the quality of surgical treatment which had been provided to patients in the light of the need for effective and successful treatments. The research sample consisted of 40 patients with missile injuries who had reviewed: Tishreen University Hospital- Alassad Hospital Patients were divided by the area of injury (Mandible-Midface) and determined the characteristics of each injury, All of the patients were managed by primary repair in the majority of soft tissue defects. Bone repair was done primarily at the same stage using different shapes of metal stabilizers.